PENGARUH PROFITABILITAS DAN LEVERAGE TERHADAP TAX AVOIDANCE PADA PERUSAHAAN TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Reva Anastasia; Andi Basru Wawo; Safaruddin (Accounting Student Series on Emerging Trends, 2026)
This study aims to analyze the effect of Non-Performing Loan (NPL) and Loan to Deposit Ratio (LDR) on stock prices of banking companies listed on the Indonesia Stock Exchange (IDX) during the 2022-2024 period. Stock prices are viewed as a reflection of investors' perceptions of company performance and risk; therefore, financial ratios that represent asset quality and bank liquidity become important information in investment decision-making. This study employs a quantitative approach using secondary data in the form of annual financial statements and stock prices on the publication date of the annual reports. The research sample consists of 19 banking companies with a total of 57 observations, selected using purposive sampling. Data analysis is conducted using panel data regression, resulting in the Random Effect Model as the most appropriate estimation model. The results indicate that Non-Performing Loan (NPL) has a negative effect on stock prices, suggesting that an increase in credit risk reduces investor confidence. Meanwhile, Loan to Deposit Ratio (LDR) has no significant effect on stock prices, indicating that bank liquidity levels are not necessarily a primary consideration. These findings support signaling theory, where credit risk information is more strongly responded to by the market.